Synthesis of a Panel of Carbon‐13‐Labelled (Glyco)Sphingolipids. Issue 12 (6th March 2015) - Wisse, Patrick; Gold, Henrik; Mirzaian, Mina; Ferraz, Maria J.; Lutteke, Ginger; van den Berg, Richard J. B. H. N.; van den Elst, Hans; Lugtenburg, Johan; van der Marel, Gijsbert A.; Aerts, Johannes M. F. G.; Codée, Jeroen D. C.; Overkleeft, Herman S.
Abstract: The synthesis of a focussed library of sphingolipids differing in the number and position of 13 C labels is described. The synthesised sphingolipids differ in substitution at both the sphingosine amine (either palmitoylated or unmodified) and the sphingosine primary hydroxyl (unmodified or glycosylated). Moreover, 13 C atoms are incorporated into either the sphingosine or the palmitate moiety, or both. This set of compounds is intended for use in relative quantitative lipidomics studies to gain insight into sphingolipid metabolism in healthy and diseased (lysosomal storage disorders) patients and animal models. Abstract : The synthesis of a focussed library of sphingolipids differing in the number and position of 13 C labels is described. 13 C atoms are incorporated into either the sphingosine or the palmitate moiety, or both. This set of compounds is intended for use in relative quantitative lipidomics studies to gain insight into sphingolipid metabolism.